Meningkatkan Keunggulan Bersaing UMKM Melalui Digital Marketing - Ustadus Sholihin; Sudarmiatin Sudarmiatin (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research discusses examination strategies using a quantitative exploration approach in the context of MSME digital marketing. a positivist-based research method was used to investigate the influence of radical innovation on the competitive advantage of Lampit MSMEs in the North Hulu Wetland Region. Data was collected through research instruments and analyzed using the PLS investigation model. The results show that radical innovation through digital marketing has a significant impact on the competitive advantage of MSMEs. This research provides important insights for MSMEs in utilizing digital marketing to increase their competitiveness in an increasingly computerized market.